2023
DOI: 10.3390/v15040879
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Hematological Patterns from Up to 985 Days of Long COVID: A Cross-Sectional Study

Abstract: Long COVID affects many individuals following acute coronavirus disease 2019 (COVID-19), and hematological changes can persist after the acute COVID-19 phase. This study aimed to evaluate these hematological laboratory markers, linking them to clinical findings and long-term outcomes in patients with long COVID. This cross-sectional study selected participants from a ‘long COVID’ clinical care program in the Amazon region. Clinical data and baseline demographics were obtained, and blood samples were collected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Another study found that patients in the acute COVID-19 phase presented with eosinophilia, and EC significantly increased up to 90 days of long COVID. Subsequently, eosinophils counts decreased to basal levels after 3 months, without any other changes after 6 and 12 months of observation (133).…”
Section: Long Covid and Eosinophilsmentioning
confidence: 88%
“…Another study found that patients in the acute COVID-19 phase presented with eosinophilia, and EC significantly increased up to 90 days of long COVID. Subsequently, eosinophils counts decreased to basal levels after 3 months, without any other changes after 6 and 12 months of observation (133).…”
Section: Long Covid and Eosinophilsmentioning
confidence: 88%
“…It is worth noting that previous studies have reported contradictory findings regarding ferritin, which could be attributed to the timing of marker evaluations in relation to the acute phase of the disease. Nevertheless, understanding this issue highlights the need for further studies [ 32 , 52 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that previous studies have reported contradictory ndings regarding ferritin, which could be attributed to the timing of marker evaluations in relation to the acute phase of the disease. Nevertheless, understanding this issue highlights the need for further studies [27,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%